The Effect of Using the Thought Map Media to Improve Understanding of Qawaid for Eleventh Grade Students at Fadhila Islamic Junior High School Pekanbaru/Ta’sîru Istikhdâmi Wasîlah al-Kharîtah al-Fikriyah Litarqiyati Fahmi al-Qawâ’id Ladâ Talâmizi as-Shaffi al-Hadiya Asyara fi Madrasah Fadhîlah at-Tsânawiyah al-Islâmiyah Pekanbaru - Ahmed, Huzrin; Firdaus, Dadang; Milla, Aqila Izzatul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
It was quantitative research aiming at finding out whether Concept Map media affected to increase student qawaid comprehension at the eleventh grade of Islamic Integrated Senior High School of Fadhilah Pekanbaru. The problem in this research was the effect of using Concept Map media in increasing student qawaid comprehension at the eleventh grade of Islamic Integrated Senior High School of Fadhilah Pekanbaru. All the eleventh-grade students at Islamic Integrated Senior High School of Fadhilah Pekanbaru were the population of this research. Purposive sampling was used in this research, and the samples were 23 students. Observation, documentation, and test were used to collect data. Product moment formula was used to analyze data. It could be stated that the use of Concept Map media affected to increase student qawaid comprehension at the eleventh grade of Islamic Integrated Senior High School of Fadhilah Pekanbaru, and it was shown with the score of to (9.806) that was higher than tt (2.040). Therefore, Ha was accepted and H0 was rejected. It could be concluded that the use of Concept Map media affected to increase student qawaid comprehension at the eleventh grade of Islamic Integrated Senior High School of Fadhilah Pekanbaru